Knowledge Management and Networks: the New Iberoamerican Psychology Journal Editors Network (2010)
The recent VII Iberoamerican Congress of Psychology in Oviedo, Spain, was the scenario for the 8th Psychology Journal Editors Symposium. In this symposium, and with the aid of the Iberoamerican Federation of Psychology Associations (FIAP, in Spanish), the Psychology Journal Editors Network was created. More than 40 Iberoamerican editors gathered together in order to discuss three topics: the first one was the situation of Psychology journals in the Scopus system, upon the development of the SJR tool by the SCIMAGO group; the second was getting to know the development of the PSICOREDALYC system, and the third one was to create the aforementioned network. The text that creates the network emphasizes the promotion of cooperation among journal editors in areas such as editorial quality, content quality and management, content accessibility and visibility. The network will also have the task of carrying out actions directed towards promoting the use of our journals’ contents, strengthening educational and qualification processes for the editors, and performing activities that allow for the improvement of content evaluation processes. The agreement was signed by all the editors who attended the Symposium, coming from Argentina, Brazil, Chile, Colombia, Mexico, Nicaragua, Peru and Uruguay. The editor of Universitas Psychologica, who also arranges these symposia, was appointed to the network’s coordination, after a virtual poll among the signing editors. Being responsible for the network, I invite the editors who were unable to make it to the meeting, in order to enhance it. We also want to invite the readers to the Second International Congress of REDALYC Editors, to be held in the Chilean city of Valdivia, between the 16th and the 19th of November. The Iberoamerican Psychology Journal Editors will be able to meet there in order to discuss fostering, educational and collaborative actions. Many times have we have emphasized the need for strengthening collaboration networks in the Iberoamerican context, that will lead to improving the quality of our journals and enhancing their visibility. The use of contents being generated is a priority in the Iberoamerican editorial agenda, and the development and strengthening of national and international editors networks are a very important tool for this to happen. Wilson López-López Editor